Interlanguage Errors In Writing Recount Text Made By Second Grade Students Of SMP Al-Islam Kartasura - Wulandari, Wulandari; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
The objectives of the research are describing interlanguage errors made by second grade students of SMP Al-Islam Kartasura in their written recount text; 1) identify the types of morphological errors; 2) the types of syntactical errors; 3) the types of discourse errors; 4) describing the frequency of errors; 5) explain the dominant type of error and 6) identify the sources of errors. The type of research is descriptive qualitative research. The objects of this research are errors in writing recount text made by students. In collecting the data, the writer uses documentation technique. There are four steps to collect data, namely: the writer asks the students to write recount text with determined topic, reads the students products, identifies of error, classifies the erroneous sentences into a list and use them as the data. The collected data are analyzed by using theory of linguistic category and surface strategy taxonomy by James, Slamet the type of error theory and Brown source of errors theory. The results of the research show that the second grade students of SMP Al-Islam Kartasura make 131 errors in their compositions. There are six points as the result of this study, namely: 1) morphological error consists of wrong spelling, false friends in homophone, and code switching, 2) syntactical error consists of phrase, the use of verb, Be, pronoun, object, the use of preposition, the use of noun, the use of adverb, literal translation, 3) discourse error consists of generic structure, and component of discourse include reference and conjunction. 4) the frequency of each errors type: morphological errors consist of 27 errors or 20.61% of errors, the syntactical errors consist of 93 errors or 70.99% of errors, discourse error consist of 11 errors or 8.40% error, 5) the dominant error from all type of errors is syntactical errors, especially the use of V1 in past event with the total number of errors are 28 errors or 21.37% of errors, 6) the researcher also finds two sources of error, they are: iterlingual transfer and intralingual transfer.